Outstanding supercapacitor performance of nitrogen-doped activated carbon derived from shaddock peel. (July 2021) - Chen, Jialian; Lin, Yuting; Liu, Jinling; Wu, Dandan; Bai, Xin; Chen, Denglong; Li, Hongzhou
Highlights: Providing a convenient and high-performance strategy to synthesize nitrogen-doped interconnected porous activated carbon with high-SSA. Specific surface area is high. N-doped activated carbon improves specific surface area and electronic conductivity. N-doped activated carbon electrode has superior cycling stability and high specific capacity. Abstract: Nitrogen doping can effectively protect the pore structure of carbon materials and improve their electrochemical properties. In this work, shaddock peel-based activated carbon doped with nitrogen was obtained by a high temperature nitriding method using dopant urea. The activated carbon was characterized and tested by XRD, SEM, TEM, BET, XPS, etc. The results show that with the increase of nitrogen doping ratio, the specific surface area (SSA) of activated carbon first increases and then decreases. The SSA of activated carbon doped with triple urea is 2450.6 m 2 /g. The SSA increased by 26.7%. In the 6 M potassium hydroxide electrolyte, served as the electrode, the mass specific capacity of activated carbon doped with triple urea under the current density of 1A/g reaches 325 F/g and an outstanding cycling stability (292 F/g after 10, 000 cycles).